MANAGEMENT OF ARABIC LANGUAGE PROGRAM AT THE ARABIC LANGUAGE DEVELOPMENT PROGRAM INSTITUTE (PPBA) UNIVERSITY OF MUHAMMADIYAH MALANG - Nasution, Annisa Hasanah; Romadhon, Nur Naria Dina; Ifawati, Nur Ila; Ratnasari, Kartika (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2026)
Arabic has an important role in intellectual development. Along with the increasing need for the use of Arabic in Indonesia, PPBA UMM strives to improve the quality of Arabic language education through comprehensive program management.  Therefore, this study aims to examine the management of Arabic language programs implemented in the Arabic Language Development Program Institute (PPBA) of the Universitas Muhammadiyah Malang (UMM). This study uses a qualitative approach with a descriptive type. Data was collected through interviews, observations, and documentation. The results of the study show that: 1) PPBA UMM uses an internal curriculum designed and developed by a team of lecturers and program managers, adjusted to the needs and context of learning at UMM; 2) PPBA UMM applies a variety of teaching methods such as communicative, audiolingual, interactive, and translation-grammar to develop students' Arabic language competence; 3) PPBA UMM human resources consist of program coordinators, administrative staff, assistants, and teaching lecturers who play an important role in program management. These findings provide insight into the practice of managing Arabic language programs in higher education and can be a reference for the development of similar programs.